PENGARUH PERTUMBUHAN PERUSAHAAN, STRUKTUR MODAL DAN AGRESIVITAS PAJAK TERHADAP NILAI PERUSAHAAN - Tusolihah, Nurdilla; Hunein, Hamida (SCIENTIFIC JOURNAL OF REFLECTION : Economic, Accounting, Management and Business, 2022)
This study aims to prove empirically the effect of firm growth, capital structure and tax aggressiveness on firm value. This study uses a sample of property and real estate sub-sector companies listed on the Indonesia Stock Exchange during 2016-2020. The type of research used is quantitative research. This research uses purposive sampling. The samples studied were 8 companies and the total sample studied was 40 units of analysis. Analysis of the data in this study using regression analysis using software Eviews Version 9. The results showed that the company's growth, capital structure and tax aggressiveness together affect the value of the company. The partial test of company growth has an effect on firm value, while capital structure and tax aggressiveness have no effect on firm value.